Knowledge and attitude regarding breast feeding among lactating mothers in a rural area, Bellur - Manchegowda, Ramya; Hulugappa, Lakshmi (International Journal Of Community Medicine And Public Health, 2018)
Background: Breastfeeding has a wide range of health benefits for mothers and children. The main obstacle in raising the exclusive breastfeeding rate is lack of awareness, false belief and customs. The current study was designed to assess knowledge and attitude to breastfeeding among rural lactating mother. Methods: A descriptive study was conducted in community health centre, Bellur during July 2017 to December 2017. Lactating mother were included in the study after meeting inclusion and exclusion criteria. Data was collected using semi structured proforma by interview method. Results: Around 80% of the mothers were aware about the time of initiation of breast feeding, 56% knew about advantage of breast feeding and 70% of the mothers were aware of exclusive breast feeding. Attitude of the mothers towards breast feeding is favourable. Only 34% of the mother knew that breast feeding should be continued till 2 years. Majority i.e. 95% of the mothers were not aware regarding the breast feeding advantage to the mother. Conclusions: The study revealed that there is a lack of knowledge in continuation of breast feeding upto two years and breast feeding benefits to the mother among lactating mothers.